Toxicity and expression of oxidative stress genes in Tribolium castaneum induced by toluene, xylene, and thinner. Issue 1 (2nd January 2019) - Pajaro-Castro, Nerlis; Caballero-Gallardo, Karina; Olivero-Verbel, Jesus
ABSTRACT: Thinner is a solvent that contains toluene, xylene, and other substances. The aim of this study was to examine the toxicity of thinner, xylene, and toluene on adult red flour beetles, Tribolium castaneum (Herbst), as well as the effects of thinner and toluene on gene expression. The major compounds identified in the thinner with peak area >2% were p -xylene (6%), toluene (4%), 2, 4-dimethylheptane (3%), methylcyclohexane (2.75%), 2-methylheptane (2%), cyclohexanone (2.6%), and nonane (2.1%). Insects were exposed to solvents at 0–240 µl/L air for 4–48 hr. Animals that survived after a 4 hr exposure to 80 µl/L air were employed to determine mRNA expression using real-time PCR. Xylene was highly toxic, and the majority of the beetles did not survive 4 hr exposure at 40 µl/L air. The lethal concentration 50 (LC50 ) values for toluene, xylene and thinner at 48 hr exposure were 97.7, <40 and 99.8 µl/L air, respectively. Thinner and toluene induced lethargy and sluggish movement in treated insects, while with xylene these effects were not observed. Glutathione-S-transferase (Gst) gene expression increased after thinner and toluene exposure. Superoxide dismutase (SOD) gene expression rose after toluene exposure. These results suggest that T. castaneum provides an alternative model for the study of toxicological effects of volatile aromatic compounds.